2021
DOI: 10.3389/fonc.2021.716002
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radiotherapy Versus Moderate-Dose Radiotherapy for the Treatment of Indolent Orbital Adnexal Lymphomas

Abstract: PurposeRadiation therapy (RT) with doses ranging from 24 Gray (Gy) to 40 Gy is a proven treatment modality for indolent orbital adnexal lymphoma (IOAL), but recently the use of low dose RT (LDRT, defined as 2 Gy x 2 fractions) has become a notable alternative. However, limited data exists comparing outcomes following LDRT to moderate-dose RT (MDRT, RT dose 4 – 36 Gy). We present a single institution retrospective analysis comparing outcomes of patients with IOALs following LDRT or MDRT.MethodsA total of 36 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(36 reference statements)
5
7
0
Order By: Relevance
“…In a recent study, ultra-low versus low dose courses for indolent orbital lymphomas were compared for 36 patients. Although similar oncological outcomes were reported between groups, with a local control of 100% and a CR and 50% in the ultra-low dose group [18], acute and late toxicities were more frequent in the 24 Gy group. Moreover, some of the referred studies [14,18] included mantle cell lymphomas in addition to follicular and marginal zone subtypes.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a recent study, ultra-low versus low dose courses for indolent orbital lymphomas were compared for 36 patients. Although similar oncological outcomes were reported between groups, with a local control of 100% and a CR and 50% in the ultra-low dose group [18], acute and late toxicities were more frequent in the 24 Gy group. Moreover, some of the referred studies [14,18] included mantle cell lymphomas in addition to follicular and marginal zone subtypes.…”
Section: Discussionsupporting
confidence: 74%
“…Although similar oncological outcomes were reported between groups, with a local control of 100% and a CR and 50% in the ultra-low dose group [18], acute and late toxicities were more frequent in the 24 Gy group. Moreover, some of the referred studies [14,18] included mantle cell lymphomas in addition to follicular and marginal zone subtypes. Although not typically referred as an indolent lymphoma, there are reports that mantle cell could also be successfully managed with ultra-low dose radiotherapy due to its radiosensitivity; trials addressing the outcomes of this scheme in this particular histology are needed.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Cerrato et al retrospectively analyzed 45 patients with MALT or MZL who were treated with 4 Gy in two 2-Gy fractions as curative or palliative intent, and revealed that low-dose RT (4 Gy) resulted in an ORR of 93% (CR: 51%, PR: 42%) and a 2-year PFS and OS of 76% and 91%, respectively, without causing significant acute and late adverse effects [ 103 ]. Baron et al also showed that among 36 patients with indolent OAL (20 patients with MALT lymphoma), low-dose RT (4 Gy) resulted in a similar ORR rate (100% [CR: 50%] vs. 87.5% [CR 58.3%]) but fewer acute toxicities (6/14 [42.9%] courses vs. 20/24 courses [83.3%], p = 0.014) when compared with moderate-dose RT (21–36 Gy) [ 104 ]. Prospective studies to validate the local control rate and adverse effects of low-dose RT (4 Gy) in larger patients with MALT lymphoma are warranted.…”
Section: Clinical Efficacy Of Radiotherapy For Hp-negative Malt Lymphomamentioning
confidence: 99%
“…However, the orbital structures are uniquely sensitive to radiation and may develop toxicities including dry eye, conjunctivitis, cataracts, keratoconjunctivitis sicca, and radiation retinopathy (6). Given the competing goals of local control and minimizing ocular toxicities, the ultra-low-dose (4 Gy in 2 fractions) treatment regimen, colloquially termed "boom-boom," has been investigated (7)(8)(9)(10)(11)(12)(13). However, the efficacy of "boom-boom" regimen is still controversial, and not adopted widely.…”
Section: Introductionmentioning
confidence: 99%